Aprovechamiento de los recursos del medio ambiente para el desarrollo de las funciones básicas de los niños del primer año del centro de educación básica "Dr. Julio Alvarez Crespo" del cantón Shushufindi, provincia de Sucumbios periodo lectivo 2014 - 2015 - Lescano Reyes, Carmela Guadalupe (2015)
The present thesis makes reference to the: USE OF THE RESOURCES OF THE Environment FOR THE DEVELOPMENT OF THE BASIC FUNCTIONS OF THE CHILDREN OF THE FIRST YEAR OF BASIC EDUCATION AT "Dr. JULY FRIZZY" BASIC EDUCATION CENTER ALVAREZ OF THE CANTON SHUSHUFINDI COUNTY DE SUCUMBIOS PERIOD LECTIVO 2014 - 2015. The main problem is: How the use of the resources of the environment is related in the development of the basic functions of the children of the first year of the Center of Basic Education Dr. Julio Frizzy Álvarez? The general objective outlined in the research is: To analyze the importance of the use of the resources of the environment in the development of the basic functions in the students of first year of the center of Basic Education Dr. Julio Frizzy Álvarez of the canton Shushufindi. The investigation is of descriptive type - analytic, since it allows to determine the incidence of the use of the resources of the environment in the development of the basic functions; methods like the inductive one - deductive, analytic - synthetic, descriptive and the statistical pattern were used, techniques and instruments were applied like: the test of basic functions addressed to the children object of this study and applied surveys as much to the teachers as to the family parents; the population sample belongs to 58 girls and/or children, 58 family parents and 5 teachers giving a total of 121 people. From the basic functions test fundamentally, it was concluded that in the corporal scheme in a 88% locate the parts of the body in an appropriate way; in lateralization we could identify that 82% are right handed and the other 18% are left handed; in directionality they discriminate against in a correct way the left- right notion; in 80% they present visual discrimination and in 90% they present perception and auditory discrimination in an appropriate way; in 84% it presents a process of attention and it tiring developed. As product of the research it was determined that the resources of the environment make an impact on the appropriate way of development of basic functions, for what we should strengthen the abilities and the students' capacities in connection with the mean that surrounds them and not alone in the school but also at home, and even more inhabiting a rich scenery in natural resources.